Group counseling for gifted underachieving high school students in sequoia high school district - Finney, Ben C.; Van Dalsem, Elizabeth L. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1965)
Because of the far-reaching implications of the problems of the underachiever, it was sought to determine whether group counseling on a long-term basis would have any positive effect. Students chosen were in the top 25 percent in aptitude, with grade averages considerably below the mean. A control and an experimental group were chosen. It was hypothesized that change would be in the direction of higher grade point averages. Changes were also measured in self-concept, teacher attitudes, attendance patterns, and behavior, and study skills. The sessions took place once a week over a 2-year period. The evaluation at the end of four semesters indicated that grades and study habits did not change either on the absolute level or in comparison with the control group. Teacher ratings showed that the experimental group improved, and fewer absences were noted. The control group worsened in the psychological areas of responsibility, equalization, and maturity. The psychological inventory indicated an increase in poise, self-confidence, and in the capacity for independent thought and action for the experimental group. Although the problem of poor grades was unsolved, the evaluation and the opinions of students, parents, and the counseling staff indicate that group counseling was a positive and beneficial experience. A partial followup study of these pupils on a long-term basis in terms of vocational, personal, and educational goals will be undertaken.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Comparative Analysis; Gifted; Group Counseling; High School Students; Individual Characteristics; Student Attitudes; Student Interests; Underachievement; California (Sequoia)